A Documentation Study of Self-Care Deficits In Patients With Schizophrenia at The Arjuna Guesthouse In Yogyakarta Grhasia Mental Hospital - Tri Okfia; Nunung Rachmawati; Tenang Aristina (Health Media, 2020)
The phenomenon of mental disorders throughout the world has become a very serious problem to be observed. There are around 21 milion people experience servere mental disorders. Patients with mental disorders tend to experience problems with personal hygiene. The purpose of writing this documentation study is to find out the description of self-care defisit in patients with Mr. O schizophrenia at Wisma Arjuna Yogyakarta Grhasia Mental Hospital and to find an overview of nursing assessment, diagnosis, planning, implementation, and evaluation. This documentation study uses a descriptive qualitative method that describes a case by utilizing a nursing care report in 2017. The result obtained in the case of Mr. O with a diagnosis of self-care deficit have been resolved. The conclusion from these results is that the patient has been able to use the toiletries provided and the patient says he is more confident because he is able to decorate and dress properly.